A molecular atlas of cell types and zonation in the brain vasculature - Vanlandewijck, Michael; He, Liqun; Mäe, Maarja Andaloussi; Andrae, Johanna; Ando, Koji; Del Gaudio, Francesca; Nahar, Khayrun; Lebouvier, Thibaud; Laviña, Bàrbara; Gouveia, Leonor; Sun, Ying; Raschperger, Elisabeth; et al. (Nature (London), 2018)
Cerebrovascular disease is the third most common cause of death in developed countries, but our understanding of the cells that compose the cerebral vasculature is limited. Here, using vascular single-cell transcriptomics, we provide molecular definitions for the principal types of blood vascular and vessel-associated cells in the adult mouse brain. We uncover the transcriptional basis of the gradual phenotypic change (zonation) along the arteriovenous axis and reveal unexpected cell type differences: a seamless continuum for endothelial cells versus a punctuated continuum for mural cells. We also provide insight into pericyte organotypicity and define a population of perivascular fibroblast-like cells that are present on all vessel types except capillaries. Our work illustrates the power of single-cell transcriptomics to decode the higher organizational principles of a tissue and may provide the initial chapter in a molecular encyclopaedia of the mammalian vasculature. Single-cell transcriptomic analysis of the murine blood–brain barrier provides molecular definitions of the main vascular cell types, classifies perivascular cell types and sheds light on the organization of the arteriovenous axis. Molecular map of brain vascular cells Good vascular health is essential to proper brain function. Yet brain vascular cells have not been systematically characterized at a molecular level. Christer Betsholtz and colleagues use single-cell transcriptomics to identify the molecular profiles of the main vascular cell types in the adult mouse brain. The molecular identity and phenotype of endothelial cells change gradually along the arteriovenous axis, whereas mural cells are precisely defined either as arterial or arteriole smooth muscle cells and pericytes, or as venous smooth muscle cells. The work also provides a comprehensive molecular definition of pericytes, showing that the pericytes of one organ are highly homogeneous but quite distinct from those of a different organ. Finally, the analyses uncover a novel perivascular cell type that shares some similarities with fibroblasts and that makes up the outer layer of all brain vessels except capillaries.